Nuclear Localization of COX-2 in relation to the Expression of Stemness Markers in Urinary Bladder Cancer - Raynoo Thanan; Mariko Murata; Ning Ma; Olfat Hammam; Mohamed Wishahi; Tarek El Leithy; Yusuke Hiraku; Shinji Oikawa; Shosuke Kawanishi (Hindawi Limited, 2012)
Inflammation may activate stem cells via prostaglandin E2 (PGE2) production mediated by cyclooxygenase-2 (COX-2) expression. We performed an immunohistochemical analysis of the expression of stemness markers (Oct3/4 and CD44v6) and COX-2 in urinary bladder tissues obtained from cystitis and cancer patients with and without Schistosoma haematobium infections. Immunoreactivity to Oct3/4 was significantly higher in S. haematobium-associated cystitis and cancer tissues than in normal tissues. CD44v6 expression was significantly higher in bladder cancer without S. haematobium than in normal tissues. COX-2 was located in the cytoplasmic membrane, cytoplasm, and nucleus of the cancer cells. Interestingly, the nuclear localization of COX-2, which was reported to function as a transcription factor, was significantly associated with the upregulation of Oct3/4 and CD44v6 in bladder cancer tissues with and without S. haematobium infection, respectively. COX-2 activation may be involved in inflammation-mediated stem cell proliferation/differentiation in urinary bladder carcinogenesis.